An anaerobic in vitro flow model for studying interactions at the gastrointestinal host–microbe interface - L. L. Bang; J. S. Pettersen; N. Høiland; A. M. Rojek; D. R. Tornby; J. Møller-Jensen; U. S. Justesen; R. M. Pedersen; T. E. Andersen (npj Biofilms and Microbiomes)
Abstract In vitro research on host–microbe interactions in the human gut has been challenging due to the differing oxygen requirements of mammalian cells and intestinal microbiota. Few models of this environment have been developed, and those available are complex, limiting the extraction of important information during experiments. Here we report an in vitro model that by simple means creates an anaerobic environment for microbiota growing on living, cultured human epithelium under physiological flow. This model enables long-term co-culture of intestinal epithelial cells with obligate anaerobic bacteria, exemplified here by Clostridioides difficile and Bacteroides fragilis. Anaerobic conditions are maintained through the integration of an anaerobization unit, developed to facilitate online deoxygenation of media via liquid-to-liquid gas diffusion, eliminating the need for encapsulation in complex gas chambers. We show that stable oxygen levels of less than 1% can be maintained in the model for several days without compromising the viability of the intestinal epithelium. Furthermore, we demonstrate the performance of the model by simulating prolonged colonization with C. difficile and B. fragilis, as well as the clinically relevant persistence of C. difficile following treatment with vancomycin.